Sterile Acellular Dermal Collagen as a Treatment for Rippling Deformity of Breast - Brittany Busse; Hakan Orbay; David E. Sahar (Case Reports in Surgery)
Prosthetic implants are frequently used for breast augmentation and breast reconstruction following mastectomy. Unfortunately, long-term aesthetic results of prosthetic breast restoration may be hindered by complications such as rippling, capsular contracture, and implant malposition. The advent of use of acellular dermal matrices has greatly improved the outcomes of prosthetic breast reconstruction. We describe a case of rippling deformity of breast that was treated using an acellular dermal matrix product, AlloMax. The patient presented with visible rippling of bilateral prosthetic breast implants as well as significant asymmetry of the breasts after multiple excisional biopsies for right breast ductal carcinoma in situ. A 6×10 cm piece of AlloMax was placed on the medial aspect of each breast between the implant and the skin flap. Follow-up was performed at 1 week, 3 months, and 1 year following the procedure. The patient recovered well from the surgery and there were no complications. At her first postoperative follow-up the patient was extremely satisfied with the result. At her 3-month and 1-year follow-up she had no recurrence of her previous deformity and no new deformity.